Adaptação transcultural e validação de conteúdo do questionário “Parcours Amoureux des Jeunes - PAJ” - Montréal/ Canadá - para o contexto do Brasil - Nascimento, Ohana Cunha do (2014)
Introduction: the PAJ inventory study the path of young love, from the perspective of analyzing the relationship between violent events and relationships with family, friends and lovers. This thème has mobilized researchers in different social contexts, regions and countries, considering the violence`s impact. Researchers in this area requires the use of validated instruments, with multidimensional approach, regardless of source context, based on the experience of literature. Objective: submit the inventory PAJ "Parcour Amoreux des Jeunes" to the cross-cultural adaptation and validation of content. Methodology: protocol steps recommended were the ones that follow: (1) translation and back-translation - translation and back-translation - the translation was attended by two Brazilian researchers , skilled in French , and later , two young native Canadian researchers fluent in Portuguese, ending Pilot II version . (2) Analisys by the Expert Committee - ten professionals from different backgrounds participated (researchers in validation , adolescence and violence) , who analyzed individually , the clarity and equivalence for each question according to the characteristics of clarity (1) It is not clear , (2) It is a little unclear , (3) almost everything is clear , (4) it is clear and I have no doubt , and equivalence : (1) not equivalent , (2) Partially equivalent; " (3) equivalent . After analysis , the percentages of clarity and equivalence and Content Validity Index / general question for IVC were calculated, obtaining Pilot III version , (3) Pre -test - Pilot III was assessed by a sample of 36 young people , 14-24 years old, both genders , with the same characteristics as the target of the later stages (psychometric analysis and application to the target population) population. In the pre -test interpretive questions were analyzed , in order to obtain cultural, conceptual, semantic and idiomatic equivalence, improving, thus, the instrument comprehension. After analysis of experts and young people , proportions relative to clarity and equivalence and Content Validity Index ( CVI ) were calculated , considering as appropriate issues with grades 3 and 4 for clarity, with value above 0.78 , according literature recommendations. Results: in general, the inventory PAJ had adequate content validity (0.97), considering the recommended limit value for adequacy (0.78). All sections of the instrument showed good performance (adequacy to clarity and equivalence), except the first section (general information, sociodemographic questions the cultural context of young parents' ethnicity, education, language spoken, among others) whose items and issues experienced cross-cultural adaptation and adjustment to match the Brazilian reality. Conclusions: PAJ showed suitable validity of content. The stages of cultural adaptation, and validation of content of instrument becomes appropriate for the procedures that follow - steps of reliability assessment (psychometrics) and applicability to the youth population in the brazilian context.